A Swedish perspective on nursing and psychosocial research in paediatric oncology: A literature review. Issue 3 (June 2015) - Enskär, Karin; Björk, Maria; Knutsson, Susanne; Granlund, Mats; Darcy, Laura; Huus, Karina
Abstract Purpose A dramatic improvement in outcomes of survival rates of childhood cancer has been seen. Caring science research is central in providing skills and knowledge to the health care sector, but few overviews of the content of published research have been carried out. The aim of this review was to investigate the content and methodology of published studies in paediatric oncology relevant to caring science, and also to compare possible differences in content and method of the published studies from the nursing and psychosocial perspectives. Method A systematic literature review was performed of 137 published articles on paediatric oncology relevant to caring science in Sweden. Results The results show that most of the studies were descriptive or comparative ones with a quantitative design. Most of them focused on parents (43%) or children (28%). Most of the studies investigated wellbeing (88%), using questionnaires (54%) or interviews (38%). Several different measurement instruments had been used. While the results were often clearly presented, the clinical implications were more diffuse. The most acknowledged research fund was the Swedish Childhood Foundation (75%). Conclusions To reflect the children' perspectives in paediatric oncology require that future researchers take on the challenge of including children (even young ones) in research. The use of a limited number of agreed measurement instruments is desirable. The biggest challenge for the future is to make a shift from explorative to intervention studies. There is an urgent need to transform research results into clinical practice.